Democracy is healthier – health in Poland in the late 1980s and 1990s - Zatoński, Witold; Zatoński, Mateusz (Journal of Health Inequalities, 2016)
The collapse of the communist regime in Poland at the end of the 1980s, followed by the opening of the country to market economy, precipitated a “natural experiment” in population health. Poland emerged from communism with very poor health indicators, high rates of lung cancer and cardiovascular diseases. In the years immediately following the collapse of communism the situation deteriorated further, as a surge in alcohol consumption led to a dramatic increase in premature mortality. However, after 1991 the health situation of the Polish population began to improve. Mortality rates began to decline for all age groups, driven mainly by the decline in cardiovascular disease morbidity and mortality. One reason for this health improvement can be sought in the 10% decrease in smoking prevalence that took place in the 1990s, and was stimulated by the implementation of very progressive anti-tobacco legislation. Another contributor was the reversal in alcohol consumption trends, with alcohol consumption falling from 11 litres in 1991 to 8.5-9 litres in 1995. However, the chief reason for the rapid improvement in health were the revolutionary changes in the diet of Poles – the fall in animal fat consumption compensated by the increase in vegetable fat consumption, and the increase in the consumption of fruits and vegetable. The resulting increase in life expectancy between 1991 and 2002 among Polish women was the fastest in Europe, and among Polish men it was the third fastest.